2018
DOI: 10.1117/1.jmi.5.2.021205
|View full text |Cite
|
Sign up to set email alerts
|

Plan in 2-D, execute in 3-D: an augmented reality solution for cup placement in total hip arthroplasty

Abstract: Reproducibly achieving proper implant alignment is a critical step in total hip arthroplasty procedures that has been shown to substantially affect patient outcome. In current practice, correct alignment of the acetabular cup is verified in C-arm x-ray images that are acquired in an anterior-posterior (AP) view. Favorable surgical outcome is, therefore, heavily dependent on the surgeon's experience in understanding the 3-D orientation of a hemispheric implant from 2-D AP projection images. This work proposes a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
0
39
0
1
Order By: Relevance
“…Fotouhi J. et al [51] proposed an intra-operative AR guidance system for acetabular cup placement in total hip arthroplasty. Using two intraoperative acquired Carm X-ray images, the cup position is planned.…”
Section: Instrument / Implant Placementmentioning
confidence: 99%
“…Fotouhi J. et al [51] proposed an intra-operative AR guidance system for acetabular cup placement in total hip arthroplasty. Using two intraoperative acquired Carm X-ray images, the cup position is planned.…”
Section: Instrument / Implant Placementmentioning
confidence: 99%
“…Implementing Virtual and Augmented Reality Tools for Radiology Education and Training, Communication, and Clinical Care 571 AR-specific applications have shown promise across a number of disciplines (16,17), with emerging potential applications in medical imaging (Fig 2) (18,19). Recent advances in technology have allowed the increased portability of AR hardware, making more widespread utilization possible (19,20) The main types of AR devices include see-through head-mounted displays, mobile-based devices, and projection-based devices (21).…”
Section: Fundamentals Of Vr and Armentioning
confidence: 99%
“…Previous studies showed the validity of the one‐time calibration of an optical camera on the C‐arm . However, due to mechanical sagging of the C‐arm, the stereo extrinsic parameters between the RGBD device and the x‐ray source are subject to small changes when the C‐arm rotates to different angles …”
Section: Resultsmentioning
confidence: 99%